Mortgage lending as a financial management tool - Bella Orynbetova, Ushkyn Saidirakhman, Namazaly Omashev, Manchuk Mukasheva, (Opción, 2019)
This research investigates the development of the Kazakh press via different methods such as the examination and source analysis of the content of Kazakh newspapers from 1917 to 1925. As a result, distortion of the Kazakh language and Kazakhization prospects were identified as the most prominent issues in the studied samples. In conclusion, the analysis of the informative and stylistic content of 14 issues of Kazakh newspapers of that time shows that the most topical issues included the integrity of Kazakh lands, distortion of the Kazakh language, and the prospects of Kazakhization.